(untitled) (Research, Society and Development, 2020)
The aim of this study was to promote an experience report by implementing the nursing consultation directed at adolescents as part of the institutional routine of a Basic Health Unit. This is an experience report through an application project linked to the discipline of Nursing Internship II - Community, belonging to the Undergraduate Nursing Course at the University of International Integration of Afro-Brazilian Lusophony, developed at the Basic Health Unit Dr Dilberto Prata Mota, located in the Municipality of Redenção in the interior of Ceará, the experience took place from January to April 2019. The project was successful in its implementation so that the percentage of adolescents remained above 50% of the expected demand. In the first consultation, an average of 80% of the demand was present (number of 8 adolescents in a target of 10), followed in the second consultation of 60% (6 adolescents in a quantity of 10) and in the third consultation 60% (6 adolescents in a quantity of 10). 10) aged 11 to 20 years in terms of gender equity. The implementation of the nursing consultation is fundamental within the context of Primary Care, focused primarily on a public that needs notorious care in view of their particular needs and singularities. On the other hand, it has become enriching for the academic to promote an action of this magnitude, in order to bring benefits to the field of action, and to acquire a critical sense in the face of social problems aiming at practical and applicable resolution in each context.